2020
DOI: 10.3390/ijms21249372
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology of Atherosclerotic Ischemic Strokes

Abstract: Among the causes of global death and disability, ischemic stroke (also known as cerebral ischemia) plays a pivotal role, by determining the highest number of worldwide mortality, behind cardiomyopathies, affecting 30 million people. The etiopathogenetic burden of a cerebrovascular accident could be brain ischemia (~80%) or intracranial hemorrhage (~20%). The most common site when ischemia occurs is the one is perfused by middle cerebral arteries. Worse prognosis and disablement consequent to brain damage occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 162 publications
0
18
0
Order By: Relevance
“…Resting NLRP3 is situated at the endoplasmic reticulum. In step two, an effector domain (pyrin domain, or PYD) is oligomerized in the NLRP3 central domain, serving as a girder for ADC adaptor protein (apoptosis-associated speck-like protein containing a carboxy-terminal CARD), which combines with procaspase-1 and forms the NLRP3 inflammasome [ 146 ]. This, in turn, by using the CARD (caspase activation and recruitment domain), activates procaspase-1 to caspase-1 and splits pro-IL-1β into its active form [ 147 ], leading to pyroptosis, a specific type of cell death [ 141 ].…”
Section: Inflammation In Ischemia/reperfusion Injuriesmentioning
confidence: 99%
“…Resting NLRP3 is situated at the endoplasmic reticulum. In step two, an effector domain (pyrin domain, or PYD) is oligomerized in the NLRP3 central domain, serving as a girder for ADC adaptor protein (apoptosis-associated speck-like protein containing a carboxy-terminal CARD), which combines with procaspase-1 and forms the NLRP3 inflammasome [ 146 ]. This, in turn, by using the CARD (caspase activation and recruitment domain), activates procaspase-1 to caspase-1 and splits pro-IL-1β into its active form [ 147 ], leading to pyroptosis, a specific type of cell death [ 141 ].…”
Section: Inflammation In Ischemia/reperfusion Injuriesmentioning
confidence: 99%
“…They include tumour necrosis factor-alfa (TNF-α), interleukin (IL) 1α, IL-1β, chemokine (C-X-C motif) ligand 7 (CXCL7), chemokine (C-C motif), ligand 5 (CCL5), chemokine (C-X-C motif) ligand 4 (CXCL4), chemokine (C-X3-C motif) ligand 1 (CX3CL1), adhesion molecules, proteases, prostanoids and leukotrienes, while IL-1, IL-10, TNF-α, IL-6, IL-20, IL-17, NADPH oxidase, chemokine (C-X-C motif) ligand 8 (CXCL8), inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) are involved in the enhancement phase of this process. In addition, other molecules, including transforming growth factor β (TGF-β), IL-17, IL-10 and IL-23, mediate the resolution phase [ 18 , 19 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Pathogenetic Mechanisms Of Hypertension—brain Induced Compli...mentioning
confidence: 99%
“…Finally, some molecules such as the neutrophil-to-lymphocyte ratio family pyrin domain-containing 3 (NLRP3) inflammasome, Dickkopf WNT Signalling Pathway Inhibitor 3 (DKK-3), dectin-1, MKEY and microRNAs (miRNAs), as well as being implicated in the course of neuroinflammation [ 18 , 19 , 86 , 88 , 89 , 90 , 91 , 92 , 93 ], have shown to have interesting characteristics that can attribute a target role in the management of brain damage, and they are summarized as follows: The NLRP3 inflammasome is responsible for the activation of IL-1β and the release of IL-18, which phosphorylate insulin receptor substrate 1 (IRS-1), worsening insulin resistance and causing neuronal death. The NLRP3 inflammasome is one of the primary mediators contributing to the neuroinflammation process and consequent brain damage [ 88 ].…”
Section: Pathogenetic Mechanisms Of Hypertension—brain Induced Compli...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous amounts of evidence revealed that hypoxic-ischemic insults and neuroinflammation attribute to the pathogenic mechanisms of CVDs [ 22 , 23 ]. Increasing evidence suggests the crucial role of TLRs in the pathogenesis of AIS [ 24 , 25 ], ICH [ 26 , 27 ], and SAH [ 28 ].…”
Section: Introductionmentioning
confidence: 99%